Secretory carrier-associated membrane protein 2 (SCAMP2) regulates cell surface expression of T-type calcium channels - Cmarko, Leos; Stringer, Robin N; Jurkovicova-Tarabova, Bohumila; Vacik, Tomas; Lacinova, Lubica; Weiss, Norbert (Molecular brain, 2022)
Low-voltage-activated T-type Ca2+ channels are key regulators of neuronal excitability both in the central and peripheral nervous systems. Therefore, their recruitment at the plasma membrane is critical in determining firing activity patterns of nerve cells. In this study, we report the importance of secretory carrier-associated membrane proteins (SCAMPs) in the trafficking regulation of T-type channels. We identified SCAMP2 as a novel Cav3.2-interacting protein. In addition, we show that co-expression of SCAMP2 in mammalian cells expressing recombinant Cav3.2 channels caused an almost complete drop of the whole cell T-type current, an effect partly reversed by single amino acid mutations within the conserved cytoplasmic E peptide of SCAMP2. SCAMP2-induced downregulation of T-type currents was also observed in cells expressing Cav3.1 and Cav3.3 channel isoforms. Finally, we show that SCAMP2-mediated knockdown of the T-type conductance is caused by the lack of Cav3.2 expression at the cell surface as evidenced by the concomitant loss of intramembrane charge movement without decrease of total Cav3.2 protein level. Taken together, our results indicate that SCAMP2 plays an important role in the trafficking of Cav3.2 channels at the plasma membrane.
Keywords: vápník; vápníkové kanály - typ T; membránové proteiny; Carrier Proteins; savci; Calcium Channels, T-Type; Calcium; Cell Membrane; Membrane Proteins; Animals; Mammals; neurony; transportní proteiny; zvířata; Neurons; buněčná membrána